(Batı Felsefesi Çerçevesinde) Epistemolojik ve Etik Açıdan İnanç - Tüzer, Abdullatif (Dinî araştırmalar, 2003)
Epistemology and ethics of belief is one of the most important and serious problems in philosophy and philosophy of religion. Is there, for belief, any standard or criteion to be rational and, if any, what are? Is true and valid belief equivalent to rational belief? Is there any rational basis of religious belief and especially God-belief? Or are those irrational? What is the nature of relation between belief, knowledge and ethics? Such questions as these quoted above have been vehemently discussed and answered from different philosophical aspects and several point of views. Chief among them rationalism, pragmatism, intuitionism and fideism can be listed as remarkable and noteworthy. In this paper we have considered, of these, only two, namely rationalism and fideism. In particular, the challenging and severe argument of William K. Clifford against belief in anything upon insufficient evidence, who is a strong and radical rationalist, was explained and then we seized on four conter-argument which can be taken out of philosophical writings of some thinkers. Wittgensteinian fideism, Kierkegaard’s irrationalism, Pascal’s argument of wager and moral evidence of Kant are those. And occasionally we criticised all the views and drew some conclusion and finally evaluated them